Development and Implementation of a Wireless Telemetry System for a Mechanical Rover Prototype (LACCEI, 2024)
This paper outlines the design, development, testing, and deployment of a telemetry system aboard Vaughn College’s Human Exploration Rover Challenge (HERC) rover to collect information on the environment, rover, and drivers’ status. Developing this telemetry system allows the team to acquire data from a unique rover design and analyze it, simulating what a real space mission would be like. Based on the competition and design requirements, this system comprises a temperature and humidity sensor, an OV2640 camera, a Long Range (LoRa) module for communication, a Global Positioning System (GPS) sensor, and an ESP32 microcontroller. The system’s transmitter acquires all the desired data, while the receiver displays the information on the Arduino Internet of Things (IoT) cloud for analysis.